Investigation of refraction corrections in levelling by using repeatable short term height readings and the direct measurement of the temperature gradient - Καμπούρης, Αναστάσιος-Γραμματάς (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2018)
The demand of high accuracy geodetic measurements for the needs of engineering, deformation and monitoring surveying is nowadays heightened. The intense technological improvement and development of geodetic instrumentation has broadened the capabilities and prospects in the applications of the surveying engineer. Despite the fact of technological advantages the accuracy of engineering and geodetic type measurements, which are carried out either in the lower atmosphere and close to the ground or indoors and underground, is still limited because of refractive effects. The error of geodetic refraction, which bends the sighting line through any telescope, is in terms influenced by the fluctuations of the meteorological parameters that are causing air density inhomogeneity along the sighting path. The aim of this master thesis is to address a generally applicable method, regarding as much as the instrumentation configuration and the data acquisition procedure as well as the post-processing computations, in order to compute refraction corrections in spirit levelling measurements. The determination of the refraction corrections is based on the direct measurement of the temperature gradient, which is the major influential factor. Hence, both indoor and outdoor experimental tests were carried out by implementing a stand-alone set up of a high accuracy digital level and air temperature sensors nodes mounted on the barcoded invar staff. Thus, the additional time series were generated, containing repeatable short term measurements of height readings, air temperatures at certain heights and atmospheric pressure for a time period of several days and a time interval of 5 minutes. The present master thesis is consisted of and summarized by the following 5 chapters:  The first chapter introduces the effect of geodetic refraction and explains the different terminologies of the refraction among the surveyor’s practices. Moreover there is a briefing of the existing refraction correction methods while the goal of this thesis is highlighted.  The second chapter includes a thorough theoretical overview of the geodetic refraction starting from the Fermat’s principle and Snell’s law and leading to the equation of the local geodetic refraction coefficient k. Subsequently there is an analysis of the refraction correction by using the direct measurement of the temperature gradient and the corresponding temperature height functions. Lastly there is a detailed demonstration of the amplitudes of the temperature gradient and the geodetic refraction coefficient k with regard to past studies results.  The third chapter presents the air temperature sensors nodes as well as the meteorological instrumentation. Additionally a calibration procedure of the air temperature sensors is being displayed by using a climate chamber device and XVI linear modeling in order to adjust the air temperature measurements to the same reference scale.  The fourth chapter demonstrates analytically both the indoor and the outdoor experimental tests. Initially starts with the presentation of the geodetic instrumentation and the stand-alone set up and continues with the thorough illustration of the acquired datasets. Thereafter the evaluation of the temperature height functions curve fitting is introduced as well as the computations of the temperature gradient. In the end the calculated refraction corrections results are being illustrated.  The fifth chapter consists of the final conclusions and deductions of the overall process and highlights proposals and recommendations that are in the need of further investigation. In conclusion the calibration procedure of the air temperature sensors managed to improve the temperature readings by adjusting the measurements to the same reference scale. Moreover the dependence of the height readings with respect to their linear relationship of the measured meteorological parameters showed a poor and a moderate correlation with regard to atmospheric pressure and air temperature respectively. Moreover when the temperature gradient had values greater than the measuring accuracy of air temperature sensors 0.4°C∙m-1 then all the temperature height functions seemed to work properly. Additionally when this value was limited to 0.2°C∙m-1 then the models failed to pass the statistical test of the parameters, or to fit the data, or over-fitted the data, except Huggershoff’s model. Lastly none of the computed refraction corrections managed to contribute to the smoothing of the height readings time series since there is a lot of noise contained therein the data. Nevertheless the signs and the amplitudes of the corrections were in line with the theoretical and past studies values. Thus, the geodetic refraction coefficient k took accepted values from 0 to +2.4 in the outdoor tests and from -1.6 to +3.2 in the indoor tests.